PENUNTASAN TAKTIL DAN MOTORIK HALUS MELALUI METODE SENSOMOTORIK PADA KELOMPOK A2 TKIT INSAN KAMIL SIDOARJO - Endang Wahju Andjariani; Ifadoturrohmah (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2021)
The purpose of this study is to complete the development of tactile sensors and fine motor students so as not to experience developmental delays so that students can develop by the stages of development. The research method used is PTK, using 3 cycles. The object studied was a student of group A2 kindergarten with a total of 26 children. Each cycle contains planning, action, observation, and reflection. The results showed that in cycle I, students experienced a 15% increase in tactile and motoric fine sensors. Cycle II showed the development of tactile and fine motoric sensors increased by 12% while in cycle III, students experienced a 42% increase in tactile sensors and a 39% increase in the development of fine motoric, so it can be concluded that the use of sensomotoric methods can complete the development of tactile and motoric subtle sensors of class A2 students at TKIT Insan Kamil Sidoarjo.